2022
DOI: 10.1177/10760296221094030
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Triglyceride Glucose index for Coronary Artery Disease in Postmenopausal Women

Abstract: This study aimed to explore the association between the triglyceride glucose (TyG) index and coronary artery disease (CAD) in postmenopausal women. This study enrolled 869 postmenopausal women and classified them into two groups: CAD group (n  =  538) and control group (n  =  331). The TyG index was significantly higher in patients with CAD than in controls ( P < 0.05).Receiver operator characteristic curves showed that the TyG index was more discriminative for CAD than for control group, and after adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
(64 reference statements)
1
7
1
Order By: Relevance
“…Our study found that higher TyG index has significant association with increased risk of future CVD, and this association was attenuated but remained significant after adjusting for HDL-C. The result which derived from a retrospective study including 869 postmenopausal women is similar with our result, and demonstrated that the TyG index may be a predictor of coronary artery disease risk [ 24 ]. We found a study including 15,288 postmenopausal women who had a median age of 64 years showed HOMA-IR remained associated with high risk of CVD after adjusting for most CVD risk factors, whereas this association was not significant after adjusting for HDL-C (HR, 1.06; 95% CI 0.98–1.15) [ 7 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our study found that higher TyG index has significant association with increased risk of future CVD, and this association was attenuated but remained significant after adjusting for HDL-C. The result which derived from a retrospective study including 869 postmenopausal women is similar with our result, and demonstrated that the TyG index may be a predictor of coronary artery disease risk [ 24 ]. We found a study including 15,288 postmenopausal women who had a median age of 64 years showed HOMA-IR remained associated with high risk of CVD after adjusting for most CVD risk factors, whereas this association was not significant after adjusting for HDL-C (HR, 1.06; 95% CI 0.98–1.15) [ 7 ].…”
Section: Discussionsupporting
confidence: 86%
“…It may be explained by that, near half of female participant were over 50 years of age and susceptible to menopause in the baseline. Insulin resistance and higher CHD risks can occur after menopause due to decreasing estrogen levels [34,35,43,44,48]. Also, TyG-index was an independent risk fact or for CHD until model II in non-diabetic participants.…”
Section: Tyg-index and Gendermentioning
confidence: 92%
“…A combination of these two factors, TyG-index, demonstrated 96.5% sensitivity and 85% specificity for detecting insulin resistance, a better performance than HOMA-IR [40]. Resistance to insulin can trigger inflammatory processes, lipid metabolism deregulations, sympathetic nervous system over-activation, endothelial dysfunction and event ually, thrombosis [32,34,35,40,[43][44][45][46]. Therefore, TyG-index can serve as a simple, practical, cost-effective, reproducible, and reliable surrogate marker for IR measurement in CHD prevention plans [43].…”
Section: Mechanismsmentioning
confidence: 99%
“…The risk is associated with insulin resistance and related disorders like hyperglycemia, dyslipidemia, and hypertension (2, 3 and 4). Insulin resistance (IR) is the principal feature of metabolic syndrome and it can independently predict the development of CVD (5, 6, 7, 8). Thus, IR is a pathogenic cause and also a predictor of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is the main feature and has a significant pathogenic link to type 2 diabetes mellitus (T2DM) (3). Therefore, the early identification of individuals with insulin resistance will be essential to reduce the disease burden of CVD {2} Increasing evidence in postmenopausal women suggests a protective effect of endogenous estrogen against CAD, whereas its deficiency exacerbates the process of CAD after menopause (6).…”
Section: Introductionmentioning
confidence: 99%